EVALUASI PELAKSANAAN PROGRAM KESEHATAN DAN KESELAMATAN KERJA DI RUMAH SAKIT UMUM DAERAH TIDAR KOTA MAGELANG - Prayitno, Prayitno; Widiastuti, Nur (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
The purpose of this study was to evaluate the implementation of the Occupational Health Safety program at the Tidar Regional General Hospital, Magelang City, to analyze the constraints that caused the implementation of the Occupational Health Safety program at the Tidar Regional General Hospital, Magelang City to be not optimal, to formulate efforts to overcome the obstacles. Obstacles that arise in the implementation of the Occupational Health safety program at the Tidar Regional General Hospital, Magelang City. As a result, the implementation of SMK3 (K3 Management System) at the Tidar Hospital in Magelang City has been implemented according to applicable regulatory standards and especially Permenkes No. 66 of 2016 regarding SMK3 in Hospitals which consists of K3RS Policy Determination, K3RS Planning, K3RS Plan Implementation, K3RS Performance Monitoring and Evaluation, and K3RS Performance Review and Improvement, but it is still not optimal marked by several activities that have not been implemented properly and are still happening K3 incident. Efforts to overcome the obstacles that arise in the implementation of the Occupational Health safety program at the Tidar Regional General Hospital, Magelang City, include conducting socialization and training on OHS, socializing regularly to all employees/staff about the importance of reporting any work accident incidents at Tidar Hospital, the availability of appropriate funds for the implementation of SMK3 at Tidar Hospital, the management needs to determine sufficient human resources in the OHS Committee so that the implementation can run smoothly, provide increased competition in the OHS field for Tidar Hospital employees, Magelang City, hold a Meeting/safety toolbox induction at the start of work.